Królewskie sny, czyli „marzenie obywatela współczesnej Polski o mądrym, sprawiedliwym władcy” - Zwierzchowski, Piotr (Załącznik Kulturoznawczy, 2022)
The television series Royal Dreams directed by Grzegorz Warchoł was created in 1988. The script was written by Józef Hen who, a year later, published a novel under the same title based on the series. When telling about Władysław II Jagiełło, King of Poland in 1386–1434, Hen first of all presented a timeless, in his opinion, ethical and political ideal, in which power was based on ethics, authority and pragmatism. Based on a textual analysis, the article is aimed at reconstructing the abovementioned ideal and methods of creating it as well as ethical and historiosophical meanings related to it. In turn, a contextual analysis was used to interpret this ideal in the context of the situation in Poland in the late 1980s, when the serial and the novel came into being. Hen presents Jagiełło as a pragmatic ruler, though emphasizes that his greatness was also determined by his ethics, morality and authority originating not from the attributes of royal power, but from Jagiełło himself. He shows the importance of realizing the limitations of royal power. He also praises the king’s mature age because the wisdom and experience that age brings result in a way of seeing the world that is based on self-reflection, strengthens the attitude of a sage and forms part of the ruler’s image. However, one should remember that for Hen equally important as historical processes is the history of an individual presented against the background of the epoch, a specific microhistory. Thus, he presents Jagiełło not only as a historical and political figure, but in the context of a specific, really existing human fate. Hen was primarily concerned with revealing the truth about the character that fascinated him, but Royal Dreams can also be read in the context of the present times. By no means the thing is simple analogies, translating historical events into current ones or straightforwardly evaluating the political situation in the second half of the 1980s. Royal Dreams clearly expresses the sense of the coming of the time of the twilight of a certain epoch and the imminent birth of a new reality. However, the thing is not the prophetic dimension either, but the ethical and historiosophical one, to show the importance of a wise, responsible and strong leader in such an exceptional time. The title of the series and the novel can be read in two ways. This is not only about the king’s dreams about a strong state and his awareness of change, but also the dream about the king, “the dream of a citizen of contemporary Poland about a wise and just ruler” who will make right decisions, and his authority will make others obey him.